Low temperature glycerol steam reforming on bimetallic PtSn/C catalysts: On the effect of the Sn content. (15th April 2017) - Pastor-Pérez, Laura; Sepúlveda-Escribano, Antonio
Graphical abstract: Highlights: Bimetallic PtSn/C catalysts have been prepared and tested in the glycerol steam reforming reaction. Sn become detrimental if a too high amount of this promoter is present. Sn promoted WGS reaction and inhibited reactions that form coke precursors. A strong Pt-Sn interaction improved the stability of the catalysts operating at harsher conditions. Abstract: Steam reforming of glycerol to produce syngas or H2 -enriched streams is a promising route that has caught the attention of many researchers around the world. This reaction is typically carried out over metal-based catalysts supported on stable materials. Herein we report a study on the effect of Sn on the catalytic properties of Pt/C in the aforementioned reaction. A series of Pt-Sn/C catalysts with different Pt:Sn ratios were prepared and characterized using ICP, H2 -TPR, TEM and XPS techniques, and they were tested in the glycerol steam reforming reaction at 623 K and atmospheric pressure. The best performance was observed for the catalysts with low tin contents. It was found that Sn promoted oxidation reactions and inhibited methanation. Furthermore, the presence of Sn improved the stability of the catalysts when operating at harsher conditions of temperature and glycerol concentration. A promoter effect of Sn hindering platinum sintering and the formation of coke precursors is proposed as the origin of the observed behaviour.